Advances in cardiac organoid research: implications for cardiovascular disease treatment - Ziteng Huang; Keran Jia; Yadan Tan; Yang Yu; Wudian Xiao; Xiangyu Zhou; Jingyan Yi; Chunxiang Zhang (Cardiovascular Diabetology)
Abstract Globally, cardiovascular diseases remain among the leading causes of mortality, highlighting the urgent need for innovative research models. Consequently, the development of accurate models that simulate cardiac function holds significant scientific and clinical value for both disease research and therapeutic interventions. Cardiac organoids, which are three-dimensional structures derived from the induced differentiation of stem cells, are particularly promising. These organoids not only replicate the autonomous beating and essential electrophysiological properties of the heart but are also widely employed in studies related to cardiac diseases, drug efficacy testing, and regenerative medicine. This review comprehensively surveys the various fabrication techniques used to create cardiac organoids and their diverse applications in modeling a range of cardiac diseases. We emphasize the role of advanced technologies in enhancing the maturation and functionality of cardiac cells, ensuring that these models closely resemble native cardiac tissue. Furthermore, we discuss monitoring techniques and evaluation parameters critical for assessing the performance of cardiac organoids, considering the complex interactions within multi-organ systems. This approach is vital for enhancing precision and efficiency in drug development, allowing for more effective therapeutic strategies. Ultimately, this review aims to provide a thorough and innovative perspective on both fundamental research and clinical treatment of cardiovascular diseases, offering insights that could pave the way for future advancements in understanding and addressing these prevalent health challenges. Graphical abstract